(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article discusses the concept of ‘РАБОТА (WORK)’ in the Russian language. The synonymic range used around this concept has been studied systematically taking into account the social, philosophical and linguistic background of the concept. The words are comparatively studied with its morphological derivatives.